Objective circulation classification of rainstorm days associated with Northeast China cold vortexes in the warm seasons of 2000–19 - Huang, Lijun; Cui, Xiaopeng; Chen, Liqiang; Zou, Qiangli; Yang, Yuting (Frontiers in Earth Science, 2023)
This study conducts objective circulation classifications of rainstorm days associated with Northeast China Cold Vortexes (NECVs) in the northeast of China (NEC) during the warm seasons (May–September). To determine the optimal method and number of types, the performances of ten objective circulation classification methods are first evaluated by several evaluation indexes. Self-Organizing Maps method is then used as the optimal method to classify rainstorms into 5 types. The results show that the different synoptic circulation patterns are accompanied by distinctive large-scale circulation backgrounds, precipitation characteristics, thermodynamic and moisture conditions. In type 1, the strong western Pacific subtropical high extends north to connect with the mid-latitude ridge in the east of the NEC, and a shallow trough lies in the west of the NEC. This configuration brings the most daily and hourly mean precipitation of all types. A low-pressure anomaly with an obvious trough controls the NEC in type 2, which has a higher frequency. In type 3, the low-pressure anomaly shrinks to the south of the NEC, and the NEC is controlled by the cut-off low vortex. Type 4 has the strongest hourly precipitation and features a meridional high-low-high pressure anomaly, and the narrow zonal low-pressure anomaly is in the NEC. Two low-pressure anomalies and a westerly trough can be found in type 5 and are distributed in a southwest-northeast orientation. These synoptic circulation patterns and the corresponding spatial distribution of rainstorm-day precipitation indicate that the objective circulation classification is effective in helping understand the large-scale circulation and precipitation characteristics associated with NECVs.